(untitled) (Universal International Scientific Journal, 2026)
This article examines the pedagogical and psychological foundations of the formation of students’ spiritual and moral competencies in higher educational institutions. The study analyzes models for increasing students’ social responsibility and moral stability based on the harmony of national values ​​and modern educational standards. The dynamics of spiritual and moral development and the effectiveness of leadership activities are illustrated using the experience of the Andijan State Pedagogical Institute (ADPI).